Antigenic Variants of Influenza B Virus. Issue 5885 (20th October 1973) - Schild, G. C.; Pereira, Marguerite S.; Chakraverty, Pratima; Coleman, Marion T.; Dowdle, W. R.; Chang, W. K.
Abstract : From 1967 to 1971 little antigenic variation was detected in the prevalent influenza B viruses but in December 1972 a new antigenic variant of influenza B was isolated in Hong Kong from sporadic cases of influenza. The new variant, B/Hong Kong/5/72, possessed a haemagglutinin antigen which showed considerable antigenic differences from that of former influenza B strains while its neuraminidase antigen was closely related to that of the earlier, 1967-71, isolates. The B/Hong Kong/5/72 variant became the predominant influenza B strain in the United Kingdom by early summer 1973, and in both the United Kingdom and Japan this strain was associated with outbreaks of influenza. Strains antigenically intermediate between the 1967-71 isolates and B/Hong Kong/5/72 were isolated in a number of countries, often concurrently with B/Hong Kong/5/72-like strains. Serological studies indicated that antibody to B/Hong Kong/5/72 was infrequent in the populations in the United Kingdom and the U.S.A., suggesting the possibility of future epidemic activity associated with the new variant. In addition, conventional inactivated influenza vaccines containing the older influenza B isolates given to volunteers stimulated poor antibody responses to B/Hong Kong/5/72 virus. These studies indicate the desirability of immunizing high risk patients against B/Hong Kong/5/72-like viruses before the coming influenza season. Vaccine containing the new variant influenza B strain are currently available in the United Kingdom.